Analysis of Social Aspects and Educational Values in Formulating Scholarship Policy: A Case Study in Aceh - Syaridin, Syaridin; Yusuf, Rusli; Ibrahim, Husaini; Sofyan, Hizir; Bahrun, Bahrun; Nasir, Muhammad (Jurnal Ilmiah Peuradeun, 2024)
This article analyzed the role of social aspects and educational values in scholarship policy formation, focusing on a case study of implementation in Aceh, Indonesia. The research aimed to understand the impact of integrating social and educational factors in scholarship policymaking and how this affects the effectiveness of the program in promoting educational access and equity. This study used a qualitative approach to collect data from various sources, including interviews with stakeholders, analyses of policy documents, and surveys of scholarship recipients. The focus was on how the Aceh Scholarship policy was designed to address the specific social challenges of the region, particularly the impact of post-conflict and natural disasters. The results showed that effective scholarship policies require an in-depth understanding of the social context and educational needs. The Aceh Scholarship, for example, successfully demonstrated how policies tailored to local social conditions could increase educational participation and positively impact social and economic recovery. This analysis provided important insights for policymakers, education practitioners, and donor agencies on the importance of considering social factors in designing scholarship programs.